Tropicalism and Romanticism: Francisco Mourelle de la Rúa’s Journey around the Pacific Ocean (1780-1781) Tropicalísimo y romanticismo: el viaje de Francisco Mourelle de la Rúa por el Océano Pacífico (1780-1781) - José María GARCÍA SÁNCHEZ (Cuadernos Dieciochistas)
The torrid or tropical Zone limited by the two tropics of cancer and Capricorn was imagined by the greatest powers of the 18 century, Spain, France, and Great Britain as a meeting area of the otherness where the tropical discourses, ambivalent, appeared written either with dose of ferocity and infertility, or exoticism and abundance. Francisco Mourelle de la Rua was one of the most experienced sailors that plied the international waters during the last third of the eighteenth century, one of his trips included one of the «tropical» zones par excellence, the trip embarked from San Blas in Nayarit in Mexico and his return to Manila is the object of analysis of this study. La zona tórrida o tropical limitada por los dos trópicos de capricornio y de cáncer fue imaginada por las mayores potencias del siglo XVIII, España, Francia e Inglaterra, como una zona de encuentro de la otredad donde los discursos tropicalistas, ambivalentes, aparecieron escritos con dosis o bien de ferocidad e infertilidad, o bien de exotismo y abundancia. Francisco Mourelle de la Rúa fue uno de los navegantes más experimentados que surcaron las aguas internacionales durante el último tercio del siglo XViii, uno de sus viajes comprendió una de las zonas «tropicales» por excelencia, el viaje emprendido desde San Blas de nayarit en México hasta Manila y su regreso es el objeto de análisis de este estudio.